Physical activity and menopausal symptoms - Khan, Bushra E Zannat; Rahman, Md Anisur; Begum, Md Nadira; Halim, Kazi Shafiqul; Muna, Atiya Tasnim; Mostary, Kazi Fardana; Islam, Md Safikul (Bangladesh Medical Journal, 2019)
Menopause is an inevitable stage of every woman’s life. This cross sectional study was conducted to assess the relationship between physical activity and menopausal symptoms from January to December 2017. By convenient sampling total 213 post menopausal women were interviewed from Mirpur, situated at the northern part of Dhaka. Five most prevalent menopausal symptoms were joint and muscular pain (90.1%), anxiety and sleep disturbance (80.3%), chest discomfort as well as physical and mental exhaustion (78.9%). Most of the respondents were physically active (63.4%), few were inactive (1.9%) and 34.7% respondents were Health Enhancing Physical Activity (HEPA) active. The mean of total Metabolic Equivalent of Task (MET)-minute per week was 2713.46 ± 1152.24 minutes. Menopausal symptoms retrieved from Menopause Rating Scale were assessed according to physical activity level. Physical and mental exhaustion was found statistically significant (p=0.04) with the higher proportion reported in divorced and widowed (90.5%). Significant relationship between psychological subscale and educational status was seen (p=.03). There was significant association between dryness of vagina and educational status (p<0.01). Physical and mental exhaustion and heart problems were found to be significantly higher among working women (p<.05). The relationship between BMI (Body Mass Index) and hot flash was found statistically significant (p<0.001). Significant statistical difference also was found between irritability and increase in BMI (p <0.001). Hot flash (p=0.001) and depression (p=0.002) were found to be statistically significant in relation with tobacco use. Uro genital symptoms ( p=.03), hot flash (p=0.01) and depression (p=0.009) were found to be statistically significant in relation with history of chronic disease. Only urinary problems were found statistically significant with HRT use. (p >.05). Anxiety was found statistically significant (p=.04) with highest proportion found in HEPA active women (89.2%). Proportion of sleep problems (100%), physical and mental exhaustion (100%), bladder problems (urinary incontinence) (75%), joint and muscular discomfort (100%) were more in inactive than minimally active and HEPA active women but the relationships were not statistically significant (p>.05). The result indicates that physical activity may have some role in reducing menopausal symptoms. Bangladesh Med J. 2018 Jan; 47 (1): 11-17